Phosphate Import in Plants: Focus on the PHT1 Transporters - Nussaume, Laurent; Kanno, Satomi; Javot, Hélène; Marin, Elena; Nakanishi, Tomoko M.; Thibaud, Marie-Christine (Frontiers in Plant Science, 2011)
The main source of phosphorus for plants is inorganic phosphate (Pi), which is characterized by its poor availability and low mobility. Uptake of this element from the soil relies heavily upon the PHT1 transporters, a specific family of plant plasma membrane proteins that were identified by homology with the yeast PHO84 Pi transporter. Since the discovery of PHT1 transporters in 1996, various studies have revealed that their function is controlled by a highly complex network of regulation. This review will summarize the current state of research on plant PHT1 multigenic families, including physiological, biochemical, molecular, cellular and genetics studies.